Sharing of Inter-state River Water Resources: Case Studies of Two Major Irrigation Systems in Tamil Nadu, India - S. SANTHANA BOSU
Water flows according to physical laws of nature and it does not respect the political or administrative boundaries created by man. Sharing of water resources is one of the major challenges to be focused on for the survival of mankind. Most of the rivers in southern India originate from the Western Ghats, and two river systems in Tamil Nadu the Cauvery Mettur Project (CMP) and Periyar Vaigai Project (PVP)D are considered here. In both systems, the catchment area being in neighbouring states, their water potential is entirely dependent on monsoon rains in the other area as well as good neighbourliness between the states water sharing. The Cauvery water dispute has become a highly sensitive issue leading to dwindling of the rice cultivated area, exportation of landless agricultural labour, change in cropping strategy and techniques of cultivation, drinking water problems etc. A portion of the surplus water from the westward-_ owing Periyar river in Kerala State is stored and diverted through a tunnel across the Western Ghats to bener t the d rought-prone areas on the eastern side in Tamil Nadu. A multidisciplinary approach beyond the physical boundaries of the basin should be considered to solve the shared water resources problems.